UNIT 30.4 Ligand‐Directed Profiling of Organelles with Internalizing Phage Libraries. (2nd February 2015) - Dobroff, Andrey S.; Rangel, Roberto; Guzman‐Roja, Liliana; Salmeron, Carolina C.; Gelovani, Juri G.; Sidman, Richard L.; Bologa, Cristian G.; Oprea, Tudor I.; Brinker, C. Jeffrey; Pasqualini, Renata; Arap, Wadih
Abstract : Phage display is a resourceful tool to, in an unbiased manner, discover and characterize functional protein‐protein interactions, create vaccines, and engineer peptides, antibodies, and other proteins as targeted diagnostic and/or therapeutic agents. Recently, our group has developed a new class of internalizing phage (iPhage) for ligand‐directed targeting of organelles and to identify molecular pathways within live cells. This unique technology is suitable for applications ranging from fundamental cell biology to drug development. This unit describes the methods for generating and screening the iPhage display system, and explains how to select and validate candidate internalizing homing peptide. © 2015 by John Wiley & Sons, Inc.